Contribution of variant alleles of ABCB11 to susceptibility to intrahepatic cholestasis of pregnancy. Issue 4 (5th November 2008) - Dixon, P H; van Mil, S W C; Chambers, J; Strautnieks, S; Thompson, R J; Lammert, F; Kubitz, R; Keitel, V; Glantz, A; Mattsson, L-Å; Marschall, H-U; Molokhia, M; et al.
Abstract : Background: Intrahepatic cholestasis of pregnancy (ICP) has a complex aetiology with a significant genetic component. ABCB11 encodes the bile salt export pump (BSEP); mutations cause a spectrum of cholestatic disease, and are implicated in the aetiology of ICP. Methods: ABCB11 variation in ICP was investigated by screening for five mutant alleles (E297G, D482G, N591S, D676Y and G855R) and the V444A polymorphism (c.1331T>C, rs2287622) in two ICP cohorts (n = 333 UK, n = 158 continental Europe), and controls (n = 261) for V444A. PCR primers were used to amplify and sequence patient and control DNA. The molecular basis for the observed phenotypes was investigated in silico by analysing the equivalent residues in the structure of the homologous bacterial transporter Sav1866. Results: E297G was observed four times and D482G once. N591S was present in two patients; D676Y and G855R were not observed. The V444A polymorphism was associated with ICP (allelic analysis for C vs T: OR 1.7 (95% CI 1.4 to 2.1, p<0.001)). In addition, CC homozygotes were more likely to have ICP than TT homozygotes: OR 2.8 (95% CI 1.7 to 4.4 p<0.0001). Structural analyses suggest that E297G and D482G destabilise the protein fold of BSEP. The molecular basis of V444A and N591S was not apparent from the Sav1866 structure. Conclusions: Heterozygosity for the common ABCB11 mutations accounts for 1% of European ICP cases; these two mutants probably reduce the folding efficiency of BSEP. N591S is a recurrent mutation; however, the mechanism may be independent of protein stability or function. The V444A polymorphism is a significant risk factor for ICP in this population.